PANDANGAN MENUTUP AURAT PASANGAN DALAM PERSPEKTIF AL-QUR'AN: STUDI TENTANG AYAT-AYAT LIBAS (PAKAIAN) - Yuhana, Laili (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2023)
Abstract. Libas can mean clothing, mixing and covering. Libas originally meant cover. Whatever is covered, the function of clothing as a covering is very clear. However, it should be noted that this does not necessarily mean